The Influence of Islamic Branding, Price, Halal Label and Location on the Decision to Buy "Sacred" Bottled Water in the Annuqayah Student of the Sawajarin - Hasanah, Nufiatul; Purnama Sari, Dia; Zahiroh; Isnainisulusiah, Anna (Asian Journal of Law and Islamic Finance, 2025)
This study aims to analyze the influence of Islamic branding, price, halal labels, and location on the purchase decision of "Suci" brand Bottled Drinking Water (AMDK) in students of the Annuqayah Islamic Boarding School in the Sawajarin Guluk-Guluk area. A quantitative approach was used in this study by collecting data through questionnaires to 169 respondents. The results of the research are expected to contribute to the development of marketing strategies based on Islamic values and understand the dominant factors that influence consumer behavior in the context of Islamic boarding schools. Multiple linear regression analysis is used to test the simultaneous and partial influence of each independent variable on purchasing decisions. The findings of this study are expected to be a foundation for manufacturers in increasing product competitiveness by considering Islamic value factors, competitive prices, halal label clarity, and strategic location.